1p36 deletion syndrome: Review and mapping with further characterization of the phenotype, a new cohort of 86 patients. Issue 2 (11th November 2022) - Jacquin, Clémence; Landais, Emilie; Poirsier, Céline; Afenjar, Alexandra; Akhavi, Ahmad; Bednarek, Nathalie; Bénech, Caroline; Bonnard, Adeline; Bosquet, Damien; Burglen, Lydie; Callier, Patrick; Chantot‐Bastaraud, Sandra; et al.
Abstract: Chromosome 1p36 deletion syndrome (1p36DS) is one of the most common terminal deletion syndromes (incidence between 1/5000 and 1/10, 000 live births in the American population), due to a heterozygous deletion of part of the short arm of chromosome 1. The 1p36DS is characterized by typical craniofacial features, developmental delay/intellectual disability, hypotonia, epilepsy, cardiomyopathy/congenital heart defect, brain abnormalities, hearing loss, eyes/vision problem, and short stature. The aim of our study was to (1) evaluate the incidence of the 1p36DS in the French population compared to 22q11.2 deletion syndrome and trisomy 21; (2) review the postnatal phenotype related to microarray data, compared to previously publish prenatal data. Thanks to a collaboration with the ACLF (Association des Cytogénéticiens de Langue Française), we have collected data of 86 patients constituting, to the best of our knowledge, the second‐largest cohort of 1p36DS patients in the literature. We estimated an average of at least 10 cases per year in France. 1p36DS seems to be much less frequent than 22q11.2 deletion syndrome and trisomy 21. Patients presented mainly dysmorphism, microcephaly, developmental delay/intellectual disability, hypotonia, epilepsy, brain malformations, behavioral disorders, cardiomyopathy, or cardiovascular malformations and, pre and/or postnatal growth retardation. Cardiac abnormalities, brain malformations, and epilepsy were more frequent in distal deletions, whereas microcephaly was more common in proximal deletions. Mapping and genotype–phenotype correlation allowed us to identify four critical regions responsible for intellectual disability. This study highlights some phenotypic variability, according to the deletion position, and helps to refine the phenotype of 1p36DS, allowing improved management and follow‐up of patients.